The Community Structure of Sea Urchin (Echinoidea) in Seagrass Ecosystem at Batu Jimbar Beach Sanur Denpasar - Sang Ayu Made Putri Suryani; Rosito Da Costa Freitas; I Made Kawan (SEAS (Sustainable Environment Agricultural Science), 2022)
Abstract This study aims to determine the intensiveness of sea urchins (Echinoidea) and the community structure of sea urchins in the seagrass ecosystem at Batu Jimbar beach, Sanur, Bali Province. In this study, the stations were determined based on the distribution and cover of seagrass so that there were three stations, namely station I located at the coordinates 115 ° 15'58.17 "E - 8 ° 41'52.87"S, while station II was located at coordinates 115 ° 15'59.34 "E - 8 ° 41'48.15"S, and Station III is located at coordinates 115 ° 16'0.16 "E - 8 ° 41'43.42"S. Sampling was carried out at the lowest tide at the three stations and analyzed using species composition, density, relative density, diversity index, uniformity index, and dominance index.The research results were found 8 types of sea urchins were found consisting of 4 families, namely the Diadematidae family (Echinothrix calamaris, Diadema setosum, Diadema savignyi and Diadema palmeri), Toxopneustidae family (Tripneustes gratilla and Pseudoboletia maculata), Echinometridae family ((Echinometra mathaei) and Stomopneustidae family (Stomopneustes variolaris).The highest density of sea urchins was in Diadema setosum as many as 149 individuals from the three stations with a density value of 0.40 individuals / 375 m2 , while the lowest density for sea urchins was 1 individual / 375 m2 . The highest relative density was in the type of Diadema setosum as much as 149 individuals / 375 m2 and the lowest relative density was in the type of Diadema palmeri as many as 1 individual / 375 m2. The structure of the sea urchin community on Batu Jimbar beach, Sanur shows that from all stations, the value of diversity is moderate with a value of 1.65, the uniformity value is not evenly distributed with a value of 0.00349 and a dominance value of 0.22 it can be concluded that there are no species. which dominates at Batu Jimbar beach in Sanur.